Reconstruction of light and polarized ion beam injection system of JINR Nuclotron-NICA accelerator complex - Andreev, V.A.; Balabin, A.I.; Butenko, A.V.; Dyubkov, V.S.; Govorov, A.I.; Golovensky, B.V.; Kobets, V.V.; Kolomiets, A.A.; Koshelev, V.A.; Kovalenko, A.D.; Kozlov, A.V.; Kropachev, G.N.; et al. (Вопросы атомной науки и техники, 2013)
The NICA ion collider project at JINR is under development at present. As a part of the project the Nuclotron injector upgrade has been started. The work is provided in cooperation of JINR, MEPhI and ITEP. Up to now the Nuclotron injection system consist of a number of proton and ion sources, the 650 keV pulsed preinjector and DTL linac LU-20 (Alvarez type). Such system provides injection into Nuclotron of 20 MeV proton and 5 MeV/u (Z/A >0.3) ion beams. The ion beam acceleration is realized at the 2nd harmonic of bunch travelling mode. The 650 kV high-voltage platform will be replaced by new RFQ structure. The R&D of this system is discussed in the report. Results of beam dynamics simulation in RFQ and MEBT between RFQ and LU-20, electrodynamics simula-tion, construction of RFQ resonator, RF feeding system construction will be presented. The RF power system is assembled and tested at equivalent load and RFQ resonator manufacturing is started.